Hubungan Antara Perawatan Luka Perineum, Pola Makan dan Kepatuhan Minum Obat dengan Penyembuhan Luka Perineum pada Ibu Nifas di RSIA Aura Syifa Kabupaten Kediri - Rena Oki Alestari (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2020)
Post Partums often times lead to Perineum wound, the wound requires the appropriate treatment, ballance diet and drinking medicine obedience. The field survey field showed infection marks, such as Kalor, Dolor, Tumor and Functiolesa. This study proves whether there is a relation between Perineum wound treatment, diet, drinking medicine obedience and Perineum wound treatment for Post Partummother at Aura Syifa Hospital, Kediri regency 2013. This study is a Corelation Analytic research. The total of population in this study is as many as 35 respondents, and the number of the sample is 30, selected by using Acidental Sampling method. Measured variable is Perineum wound treatment, diet and drinking medicine obedience as the independent variables, while the dependent variables are Perineum wound treatment. The result of this study is the good Perineum wound treatment, which is as much as 56.7%, while the good diet treatment as much as 56.7%, the drinking medicine obedience is as much as 60%, and the quick cure of Perineum wound as much as 66,7%. The statistical test used in this research is Non-Parametrik statistical test Spearment Rho Treatment with the Data Analysis Measurement result using SPSS, r=0.465. Sig. (2 – taileted) = 0.010 meaning H0 is rejected and H1 is accepted, so there is a relation between Perineum wound treatment and Perineum wound cure. r=0.465. The relation between Perineum wound treatment with Perineum wound cure is at the average level. The result of the data analysis using SPSS, r = 0.294. Sig. (2 – taileted) = 0.211, meaning H0 is accepted and H1 is rejected, so that there is no relation between diet and Perineum wound treatment. The result of the data analysis using SPSS, r = 0.478. Sig. (2 – taileted) = 0.008 meaning H0 is rejected and H1 is accepted, thus there is a relation between drinking obedience and the Perineum wound treatment. r = 0.478, the relation between drinking obedience and Perineum wound cure is at the average level.